Efficient high‐throughput biological process characterization: Definitive screening design with the Ambr250 bioreactor system. (15th July 2015) - Tai, Mitchell; Ly, Amanda; Leung, Inne; Nayar, Gautam
<x xml:space="preserve">Abstract</x> The burgeoning pipeline for new biologic drugs has increased the need for high‐throughput process characterization to efficiently use process development resources. Breakthroughs in highly automated and parallelized upstream process development have led to technologies such as the 250‐mL automated mini bioreactor (ambr250™) system. Furthermore, developments in modern design of experiments (DoE) have promoted the use of definitive screening design (DSD) as an efficient method to combine factor screening and characterization. Here we utilize the 24‐bioreactor ambr250™ system with 10‐factor DSD to demonstrate a systematic experimental workflow to efficiently characterize an Escherichia coli (E. coli) fermentation process for recombinant protein production. The generated process model is further validated by laboratory‐scale experiments and shows how the strategy is useful for quality by design (QbD) approaches to control strategies for late‐stage characterization. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1388–1395, 2015